SURFACE SEDIMENT QUALITY IN SEABED AROUND THO CHU ISLANDS, KIEN GIANG PROVINCE - Vinh, Le Thi; Tam, Pham Huu (Vietnam Journal of Marine Science and Technology, 2016)
Analysis results of surface sediment samples collected in October, 2013 in the coral reefs and soft bottom habitats around Tho Chu islands showed that silt - clay - ration, pH, Eh, organic matter contents, heavy metals, oil-grease and total sulphur in sediments ranged widely (silt - clay - ration: 1.68 - 39.28%; pH: 7.15 - 8.18; Eh: (-121.0) - (-58) mV; org C: 0.07 - 0.7%; org N: 149.4 - 242.2 μg/g; total P: 95.8 - 795.7 μg/g; Zn: 3.2 - 17.4 μg/g; Cu: 2.8 - 10.0 μg/g; Pb: 2.9 - 17.1 μg/g; oil-grease: 89 - 153 μg/g and total S: 437.6 - 3078.3 μg/g). The contents of organic matters and heavy metals (Zn, Cu) in soft bottom habitats were relatively higher than those in the coral reefs while pH values were lower. There were no differences in contents of total S, Pb, oil-grease and silt - clay - ration of sediments in two ecosystems. Overall, the sediment quality in the coral reefs and soft bottom habitats around Tho Chu islands was very good, the contents of organic matters and heavy metals in the sediments were suitable for aquatic life conservation.